Identifying the obstacles to the development of Selemak village as a tourism village in Deli Serdang regency - Kairi, Nur Khafizha; Simamora, Nuryeni; Ritonga, Pitri Wijaya (YAYASAN MITRA PERSADA NUSANTARA, 2023)
The development of tourist villages is one of the efforts made by the government to increase tourism potential in an area. As an area included in the development of the tourism village, Selemak village continues to manage and develop existing potential and continues to improve facilities and attractions to support the development of tourism village. The purpose of this research is to identify the obstacles, namely all the obstacles that are experienced in the development of a tourism village in Deli Serdang regency. The research method in this study is a qualitative approach and the data collection technique used is primary data through pre-existing data and through interviews and observations, while for secondary data collection this research is document study. The results of this study are that Selemak tourism village still has tourism potential to be developed again and can be optimized, amenities related to various supporting facilities for a destination to meet the needs of tourists, lack of availability and ease of development accessibility, obstacles in the development of accommodation namely lack of skilled manpower in the village, because having skilled and qualified human resources is an important aspect in accommodation management.